Reliable Monitoring of the Transition Zone Between Fresh and Saline Waters in Coastal Aquifers. Issue 3 (11th June 2013) - Levanon, Elad; Yechieli, Yoseph; Shalev, Eyal; Friedman, Vladimir; Gvirtzman, Haim
Abstract This study deals with the reliability of monitoring the transition zone between fresh and saline waters in coastal aquifers, considering the effect of tides in long‐perforated boreholes. Electric conductivity (EC) fluctuations in the coastal aquifer of Israel, as measured in long‐perforated borehole, were found to have the same periodicities as the sea tide, though some orders of magnitude larger than sea‐level or groundwater level fluctuations. Direct measurements in the aquifer through buried EC sensors demonstrate that EC measurements within the long‐perforated boreholes might be distorted due to vertical flow in the boreholes, whereas actual fluctuations of the transition zone within the aquifer are some orders of magnitude smaller. Considering these field data, we suggest that monitoring of the transition zone between fresh and saline water adjacent to the sea through long‐perforated boreholes is unreliable. EC fluctuations in short‐perforated boreholes (1 m perforation at the upper part of the transition zone) were somewhat larger than in the aquifer, but much smaller than those in the long‐perforated borehole. The short‐perforation diminishes the vertical flow and the distortion and therefore is more reliable for monitoring the transition zone in the shoreline vicinity.